2015
DOI: 10.2319/100414-711.1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of microbial contamination of orthodontic brackets as received from the manufacturer using microbiological and molecular tests

Abstract: Objective: To test the null hypothesis that orthodontic brackets as supplied by manufacturers do not have microbial contamination. Materials and Methods: The sample comprised 140 brackets of four different commercially available brands, used directly from the manufacturer's packaging, divided into 14 groups (n 5 10 brackets each). Of the 140 pieces, 60 were full cases and 80 were replacement brackets. Materials were tested to detect bacterial growth, analyze types of bacteria present (biochemical test), and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…Contamination with Staphylococci mostly occurs due to skin contact during manufacturing and/or packaging of orthodontic appliances [1, 6]. Similar studies conducted in this regard reported that Staphylococci were the common organisms to contaminate the orthodontic brackets [1, 3, 14]. In our study, B. cereus and B. licheniformis were the other frequently isolated organisms from the orthodontic brackets, followed by Streptococci.…”
Section: Discussionsupporting
confidence: 72%
“…Contamination with Staphylococci mostly occurs due to skin contact during manufacturing and/or packaging of orthodontic appliances [1, 6]. Similar studies conducted in this regard reported that Staphylococci were the common organisms to contaminate the orthodontic brackets [1, 3, 14]. In our study, B. cereus and B. licheniformis were the other frequently isolated organisms from the orthodontic brackets, followed by Streptococci.…”
Section: Discussionsupporting
confidence: 72%
“…There are indications (but no guidelines) concerning the reconditioning of "clinic-exposed" and "received from manufacturer" orthodontic materials (e.g. orthodontics bands, buttons, ligatures, brackets, archwires etc) (6,37,71,79,80). We believe that single-patient packaged orthodontic materials are the best choice as the EN standards define them as "single-use" and prevent their contamination by hand and environmental exposure.…”
Section: Instrument Reprocessingmentioning
confidence: 99%
“…Mostly, the coagulase-negative staphylococci are less virulent and reside on skin and mucous membranes (Al Groosh et al, 2015; Dos Santos Gerzson et al, 2015, Santos et al, 2014). Approximately 60–70% of coagulase-negative staphylococci present on the skin are S. epidermidis (Favre et al, 2005).…”
Section: Discussionmentioning
confidence: 99%